Understanding social media : how to create a plan for your business that works - Ryan, Damian (Kogan page Limited, 2015)
"Understanding Social Media is a companion title to the highly successful Understanding Digital Marketing. Accessible and practical, this book draws on the experiences of over 200 marketers to create a comprehensive guide to current practice including:- Creating a social media program - Understanding stakeholders such as blogs, networks and Web 2.0 - Rules governing the relationship between search and social - Case studies from successful and failed campaigns - Budgeting for social media activities - How to set key performance indicators (KPIs) - Understanding social media ROI - Customer experience - Building a social media team - Analytics and creating a social media dashboard - Risk assessment and risk management in social media "--